2017
DOI: 10.1590/1806-9282.63.10.899
|View full text |Cite
|
Sign up to set email alerts
|

Oral corticosteroids for asthma exacerbations might be associated with adrenal suppression: Are physicians aware of that?

Abstract: Oral cOrticOsterOids fOr asthma exacerbatiOns might be assOciated with adrenal suppressiOn: are physicians aware Of that? rev assoC med bras 2017; 63(10):899-903 899

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…There are always concerns about CS prescription and the risk of adrenal dysfunction. In a Brazilian study, the authors showed that even the use of CS for short‐term courses is associated with an increased risk of transitory suppression of the hypothalamic‐pituitary‐adrenal (HPA) axis . Nevertheless, they also highlighted that concomitant use of inhaled CS (ICS) does not impair adrenal recovery from occurring …”
Section: Pharmacokinetics and Side Effectsmentioning
confidence: 99%
“…There are always concerns about CS prescription and the risk of adrenal dysfunction. In a Brazilian study, the authors showed that even the use of CS for short‐term courses is associated with an increased risk of transitory suppression of the hypothalamic‐pituitary‐adrenal (HPA) axis . Nevertheless, they also highlighted that concomitant use of inhaled CS (ICS) does not impair adrenal recovery from occurring …”
Section: Pharmacokinetics and Side Effectsmentioning
confidence: 99%
“…bioavailability, protein‐binding affinities, plasma half‐life and metabolic inactivation and clearance) [ 13 ]. Repeat courses of OCS are also a risk factor for AI [ 18 ], and patients with a predisposition to HPA axis dysfunction as a consequence of other underlying conditions or medications may be particularly susceptible to AI caused by OCS [ 27 ]. Still, the risk of AI can be reduced, though not fully negated, by using the lowest effective dosage of OCS for the shortest amount of time [ 16 ].…”
Section: Adrenal Insufficiencymentioning
confidence: 99%
“…exacerbations. However, this use is not desirable, as repeated usage of systemic corticosteroid is associated with cumulative systemic adverse events and persistent negative impact on the hypothalamic-pituitaryadrenal (HPA) axis [10]. Nevertheless, it is difficult to avoid systemic corticosteroid use completely as it may be the last option for treatment of acute exacerbations [1,11,12].…”
Section: Management Of Severe Asthma: What Guidelines Recommendmentioning
confidence: 99%